Sludge-based composite adsorbent as well as preparation method and application thereof

By converting the elements in the sludge into materials with special structures through pyrolysis and hydrothermal methods, and combining them with a 'sandwich' structure, the problem of adsorption efficiency and life of biochar in high temperature and high humidity environments is solved, achieving low Cost and efficient sludge drying and odor adsorption effect.

CN119186492AActive Publication Date: 2024-12-27HEFEI CEMENT RESEARCH AND DESIGN INSTITUTE CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411161487.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-27
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The existing biochar adsorbents have reduced adsorption efficiency and life due to high temperature and high humidity environment during the drying process of sludge, and the cost is high, and the modification process increases costs and energy consumption.

Method used

Using sludge-based composite adsorbent, the silicon, aluminum, iron, carbon and other elements in the sludge are converted into material components with special structures through pyrolysis and hydrothermal methods, and composited with a 'sandwich' structure to improve resistance. Wet resistance to high temperature.

Benefits of technology

It has achieved efficient adsorption of sludge drying odor in high temperature and high humidity environments, reduced the production cost of adsorbents, is suitable for industrial production, and is significantly improved adsorption efficiency and life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a sludge-based composite adsorbent and a preparation method and application thereof, and relates to the technical field of solid waste resource utilization, the sludge-based composite adsorbent comprises a sludge-based molecular sieve, sludge-based perovskite and sludge ash modified sludge-based pyrolytic carbon; elements such as silicon, aluminum, iron and carbon in the sludge are fully utilized and converted into material components with special structures and functions through pyrolysis and hydrothermal methods, the material components are compounded in a sandwich structure, the moisture resistance and high temperature resistance of the biochar are remarkably improved, and the biochar has the advantages of being low in cost and high in sludge drying high-temperature and high-humidity malodorous gas adsorption efficiency. The purpose of treating waste with waste is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to a sludge-based composite adsorbent and a preparation method and application thereof. Background Art

[0002] With the continuous development of social economy and people's living standards, the output of sludge is increasing. Sludge components contain organic matter and minerals, which can be used as alternative raw materials in the cement industry to realize the resource utilization of solid waste. However, the sludge has a high water content (more than 80%), and directly entering the cement kiln will reduce the output and quality of cement. Therefore, the sludge must be dried and disposed. During the sludge drying process, a large amount of malodorous gas, mainly ammonia, will be produced and discharged, which is harmful to human health. With the continuous improvement of environmental protection and health awareness in the whole society, purifying the malodorous gas from sludge drying is a key problem that needs to be solved urgently.

[0003] In terms of comprehensive purification efficiency, economic cost, process flow, etc., the use of activated carbon-based adsorbents to adsorb and purify sludge drying odorous gases is the current main treatment method. However, activated carbon is often expensive, resulting in increased costs. Although some patented technologies use solid waste to prepare biochar as an adsorbent to reduce costs, the sludge drying odorous gas has the characteristics of high humidity and high temperature. High humidity causes a large number of adsorption sites of the adsorbent to be occupied by water molecules, and high temperature makes the adsorbate molecules have large kinetic energy and difficult to be captured by the adsorption sites, resulting in a significant decrease in the adsorption efficiency, capacity, and life of the activated carbon. At the same time, some patented technologies modify biochar, but most of them increase the adsorption capacity by expanding the pores. Since biochar has no adsorption selectivity, it is a temporary solution under the characteristics of high humidity and high temperature of sludge drying odor; the modification process requires the use of some reagents, which also increases costs. In addition, some patented technologies cool and dry the odorous gas, but the drying process increases costs and energy consumption, and cooling causes some harmful gas molecules to condense into the water with water, and polluted water treatment processes and equipment need to be deployed.

[0004] Therefore, in view of the high temperature and high humidity characteristics of sludge drying malodorous gases, it is necessary to develop a moisture-resistant and high-temperature resistant biochar-like adsorbent. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of existing biochar adsorbents in adsorbing and purifying high-temperature and high-humidity sludge drying malodorous gases, and to provide a sludge-based composite adsorbent that makes full use of elements such as silicon, aluminum, iron, and carbon in the sludge, converts them into material components with special structures and functions through pyrolysis and hydrothermal methods, and compounds them in a "sandwich" structure, which significantly improves the moisture and high temperature resistance of biochar, has the advantages of low cost and high adsorption efficiency for high-temperature and high-humidity malodorous gases from sludge drying, thereby achieving waste treatment with waste.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] One of the objects of the present invention is to provide a sludge-based composite adsorbent, comprising a sludge-based molecular sieve, a sludge-based perovskite and sludge-ash-modified sludge-based pyrolytic carbon.

[0008] The second object of the present invention is to provide a method for preparing the sludge-based composite adsorbent, comprising the following steps:

[0009] (1) mixing sludge-based molecular sieve, sludge-based perovskite, and sludge ash-modified sludge-based pyrolytic carbon with a dispersant and a binder, respectively, to prepare slurry A, slurry B, and slurry C;

[0010] (2) Slurry C, slurry B, and slurry A are sprayed on a substrate in sequence and dried to obtain the sludge-based composite adsorbent.

[0011] The third object of the present invention is to provide the use of the sludge-based composite adsorbent in purifying sludge drying odor.

[0012] The beneficial effects of the present invention are:

[0013] 1. The main gain components of the sludge-based composite adsorbent described in the present invention are all from the by-product sludge of sewage treatment plants and its incineration ash itself, which belongs to the resource utilization of solid waste, realizes waste treatment with waste, effectively reduces the production cost of the adsorbent, and has broad market application prospects.

[0014] 2. The sludge-based composite adsorbent of the present invention can effectively adapt to high temperature and high humidity environments, and is particularly suitable for the field of sludge drying and odor adsorption purification.

[0015] 3. The preparation method of the sludge-based composite adsorbent provided by the present invention has the advantages of simple operation and cheap and readily available raw materials, and is suitable for industrial production. DETAILED DESCRIPTION

[0016] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0017] The invention provides a sludge-based composite adsorbent, comprising a sludge-based molecular sieve, a sludge-based perovskite and sludge-based pyrolytic carbon modified by sludge ash.

[0018] Furthermore, the sludge-based molecular sieve, sludge-based perovskite and sludge ash-modified sludge-based pyrolytic carbon are compounded in a "sandwich" structure.

[0019] Furthermore, based on the total amount of the sludge-based composite adsorbent, the sludge-based composite adsorbent comprises 20-30 wt% of sludge-based molecular sieve and 20-30 wt% of sludge-based perovskite, and the rest is sludge ash-modified sludge-based pyrolytic carbon.

[0020] The present invention provides a method for preparing the sludge-based composite adsorbent, comprising the following steps:

[0021] (1) mixing sludge-based molecular sieve, sludge-based perovskite, and sludge ash-modified sludge-based pyrolytic carbon with a dispersant and a binder, respectively, to prepare slurry A, slurry B, and slurry C;

[0022] (2) Slurry C, slurry B, and slurry A are sprayed on a substrate in sequence and dried to obtain the sludge-based composite adsorbent.

[0023] Furthermore, in order to meet the dispersibility and adhesion of the slurry, the dispersant is ethanol; and the adhesive is Nafion solution.

[0024] Preferably, the dosage ratio of the sludge-based molecular sieve to ethanol and Nafion solution is (2-3) g: 10 mL: 1 mL; the dosage ratio of the sludge-based perovskite to ethanol and Nafion solution is (2-3) g: 10 mL: 1 mL; the dosage ratio of the sludge ash-modified sludge-based pyrolytic carbon to ethanol and Nafion solution is (4-6) g: 10 mL: 1 mL. More preferably, the dosage ratio of the sludge-based molecular sieve to ethanol and Nafion solution is 3 g: 10 mL: 1 mL; the dosage ratio of the sludge-based perovskite to ethanol and Nafion solution is 2 g: 10 mL: 1 mL; the dosage ratio of the sludge ash-modified sludge-based pyrolytic carbon to ethanol and Nafion solution is 5 g: 10 mL: 1 mL.

[0025] In order to make the adsorbent have good mechanical properties and purification performance during use, the three components of the adsorbent need to be sprayed on the substrate in the order of sludge ash-modified sludge-based pyrolytic carbon, sludge-based perovskite, and sludge-based molecular sieve to exist in a "sandwich" microstructure.

[0026] Furthermore, the substrate is one of nickel foam, carbon cloth, and honeycomb ceramics.

[0027] Furthermore, the preparation method of the sludge-based molecular sieve is as follows: take sludge ash, add dilute hydrochloric acid to adjust the pH value to 1-2, stir, filter, and dry the filter residue to obtain tempered sludge ash; take tempered sludge ash, add sodium hydroxide solid, grind and place in a tube furnace to calcine in an air atmosphere, add distilled water to the obtained calcined solid for hydrothermal crystallization, filter, and dry the filter residue to obtain the sludge-based molecular sieve. Preferably, the mass ratio of the tempered sludge ash to the sodium hydroxide solid is 1: (1-5); the calcination temperature is 600-900°C, and the calcination time is 1-3h; the mass ratio of the calcined solid to distilled water is 1: (5-20); the hydrothermal temperature is 80-120°C, and the hydrothermal time is 6-12h. More preferably, the mass ratio of the quenched sludge ash to the sodium hydroxide solid is 1:2; the calcination temperature is 700°C, and the calcination time is 1.5 hours; the mass ratio of the calcined solid to distilled water is 1:10; the hydrothermal temperature is 100°C, and the hydrothermal time is 10 hours. In the present invention, in order to ensure that the quenched sludge ash components are active, sodium hydroxide is used for hot alkali activation. The quenched sludge ash after hot alkali activation is added with distilled water for hydrothermal treatment to ensure that the sludge-based molecular sieve has a suitable growth environment.

[0028] Further, the preparation method of the sludge-based perovskite is: take sludge ash, add dilute nitric acid to adjust the pH to 1-2, stir, filter, add polytitanium chloride to the filtrate, mix, dehydrate, and pyrolyze the resulting mixture under a nitrogen atmosphere to obtain sludge-based perovskite. Preferably, the concentration of the dilute nitric acid is 0.5-2 mol / L; the mass ratio of the polytitanium chloride to the filtrate is (1-6):1; the pyrolysis temperature is 300-500°C, and the pyrolysis time is 2-6h. More preferably, the concentration of the dilute nitric acid is 1 mol / L; the mass ratio of the polytitanium chloride to the filtrate is 3:1; the pyrolysis temperature is 450°C, and the pyrolysis time is 3h. In the present invention, the addition of dilute nitric acid to sludge ash is to obtain a filtrate containing iron nitrate as one of the raw materials of perovskite; and in order to ensure that the sludge-based perovskite has a suitable growth environment and structure, it is necessary to regulate the ratio of polytitanium chloride to the filtrate.

[0029] Furthermore, the preparation method of the sludge ash modified sludge-based pyrolytic carbon is as follows: take sludge ash and sludge powder, mix them, add dilute hydrochloric acid to adjust the pH value to 1-2, stir, filter, and put the obtained solid into a tubular furnace for calcination under a nitrogen atmosphere to obtain sludge ash modified sludge-based pyrolytic carbon. Preferably, the mass ratio of sludge ash to sludge powder is 1: (5-10); the concentration of dilute hydrochloric acid is 0.5-2 mol / L; the calcination temperature is 500-700°C, and the calcination time is 1-3h. More preferably, the mass ratio of sludge ash to sludge powder is 1: 7; the concentration of dilute hydrochloric acid is 1 mol / L; the calcination temperature is 600°C, and the calcination time is 2h. In the present invention, a certain proportion of sludge ash and sludge powder is treated with dilute hydrochloric acid and co-pyrolyzed, in order to ensure that the sludge pyrolytic carbon has suitable hydrophobicity and pore volume.

[0030] Furthermore, the preparation method of the sludge ash is: calcining municipal sludge in an air atmosphere, grinding, and obtaining sludge ash. Preferably, the calcination temperature is 700-900°C, and the calcination time is 4-6 hours. More preferably, the calcination temperature is 800°C, and the calcination time is 5 hours. The total mass fraction of silicon compounds and aluminum compounds in the sludge ash is ≥50%, and the mass fraction of iron compounds is ≥7%.

[0031] Furthermore, the preparation method of the sludge powder is: drying and grinding the municipal sludge to obtain the sludge powder. Preferably, the drying temperature is 100-120°C. More preferably, the drying temperature is 105°C. In the present invention, the purpose of drying the municipal sludge is to facilitate grinding, and the purpose of calcining is to remove the organic matter therein and ensure that the active components therein are in a relatively stable state when used.

[0032] The invention provides application of the sludge-based composite adsorbent in purifying sludge drying odor.

[0033] The present invention utilizes the main elements such as silicon, aluminum, iron, carbon in the sludge and its incineration ash, and converts them into material components with special structures and functions through pyrolysis and hydrothermal methods. The main elements are sludge-based molecular sieves, sludge-based perovskites and sludge-based pyrolytic carbon modified with sludge ash, and are spatially directionally combined in a "sandwich" structure; the moisture absorption characteristics of the sludge-based molecular sieve and the heat absorption characteristics of the sludge-based perovskite phase change are utilized to allow the high-temperature and high-humidity odor to be converted into normal-temperature and low-humidity odor after passing through the sludge-based molecular sieve and the sludge-based perovskite in turn. At the same time, the pyrolytic carbon prepared by co-pyrolysis of sludge ash and sludge contains partial silicon oxide, which further improves the hydrophobicity of the pyrolytic carbon, significantly improves the moisture and high-temperature resistance of the biochar, and improves the adsorption capacity of the sludge drying odor in a high-humidity and high-temperature environment.

[0034] Example 1

[0035] (1) The sludge was dried at 105°C and then ground and passed through a 20-mesh sieve to obtain sludge powder for later use; the municipal sludge was calcined at 800°C in an air atmosphere for 5 hours, and when cooled to room temperature, it was taken out, ground, and passed through a 20-mesh sieve to obtain sludge ash for later use. After testing, the silicon oxide content in the sludge ash was 38.4%, the iron oxide content was 7.34%, and the aluminum oxide content was 17.1%.

[0036] (2) 10 g of sludge ash and 70 g of sludge powder were mixed, 1 mol / L dilute hydrochloric acid was added to adjust the pH to 1-2 and stirred for 30 min, filtered, and the obtained solid was calcined at 600 °C in a nitrogen atmosphere for 2 h to obtain sludge ash modified sludge-based pyrolytic carbon.

[0037] (3) Take 10g of sludge ash, add 1mol / L dilute hydrochloric acid to adjust the pH to 1-2 and stir for 30min, filter to obtain tempered sludge ash; mix and grind the tempered sludge ash with sodium hydroxide solid in a mass ratio of 1:2, then calcine at 700℃ in air atmosphere for 1.5h, mix the calcined solid with distilled water in a mass ratio of 1:10, hydrothermally treat at 100℃ for 10h, filter, and dry the residue to obtain a sludge-based molecular sieve.

[0038] (4) Take 10 g of sludge ash, add 1 mol / L dilute nitric acid to adjust the pH to 1-2 and stir for 30 min, filter to obtain a filtrate; mix polytitanium chloride and the filtrate in a mass ratio of 3:1, dehydrate, and then pyrolyze at 450°C in a nitrogen atmosphere for 3 h to obtain sludge-based perovskite.

[0039] (5) 3 g of sludge-based molecular sieve, 2 g of sludge-based perovskite, and 5 g of sludge-ash-modified sludge-based pyrolytic carbon were mixed with 10 mL of ethanol and 1 mL of Nafion solution in a mass ratio of 3:2:5 to prepare a slurry. The slurry was sprayed on the nickel foam in the order of sludge-ash-modified sludge-based pyrolytic carbon, sludge-based perovskite, and sludge-based molecular sieve, and then dried to obtain a sludge-based composite adsorbent.

[0040] Performance test: The obtained sludge-based composite adsorbent was placed in an adsorption test device, and 100ppm room temperature dry ammonia was introduced as a simulated odor. The results showed that after 98 minutes of adsorption, the ammonia concentration at the outlet reached 95% of the initial concentration, indicating adsorption saturation.

[0041] Example 2

[0042] The preparation method of the sludge-based composite adsorbent in this example is the same as that in Example 1.

[0043] The performance test conditions were the same as those in Example 1, except that the 100ppm room temperature ammonia was replaced with ammonia at a relative humidity of 90% and a temperature of 60°C as a simulated high temperature and high humidity odor. The results showed that after 93 minutes of adsorption, the ammonia concentration at the outlet reached 95% of the initial concentration, indicating adsorption saturation. Compared with room temperature dry ammonia, the adsorption penetration time was only shortened by 5 minutes.

[0044] Example 3

[0045] The preparation method of the sludge-based composite adsorbent in this embodiment is the same as that in Embodiment 2, except that in step (2), the mass ratio of sludge ash to sludge powder is adjusted to 1:10.

[0046] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 89 minutes of adsorption.

[0047] Example 4

[0048] The preparation method of the sludge-based composite adsorbent in this embodiment is the same as that in Embodiment 2, except that in step (3), the mass ratio of the conditioned sludge ash to the sodium hydroxide solid is adjusted to 1:1.

[0049] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 91 minutes of adsorption.

[0050] Example 5

[0051] The preparation method of the sludge-based composite adsorbent in this embodiment is the same as that in Embodiment 2, except that in step (5), the mass ratio of the sludge-based molecular sieve, the sludge-based perovskite, and the sludge-ash-modified sludge-based pyrolytic carbon is adjusted to 3:3:4.

[0052] The performance test conditions were the same as those in Example 2, except that the ammonia temperature was adjusted to 70° C. The results showed that adsorption was saturated after 86 minutes of adsorption.

[0053] Comparative Example 1

[0054] The preparation method of the sludge-based composite adsorbent in this comparative example is the same as that in Example 2, except that in step (5), the mass ratio of sludge-based perovskite to sludge-ash-modified sludge-based pyrolytic carbon is adjusted to 2:8, and sludge-based molecular sieve is not used.

[0055] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 40 minutes of adsorption.

[0056] Comparative Example 2

[0057] The preparation method of the sludge-based composite adsorbent in this comparative example is the same as that in Example 2, except that in step (5), the ratio of the sludge-based molecular sieve to the sludge-based pyrolytic carbon modified by sludge ash is adjusted to 3:7, and sludge-based perovskite is not used.

[0058] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 45 minutes of adsorption.

[0059] Comparative Example 3

[0060] The preparation method of the sludge-based composite adsorbent in this comparative example is the same as that in Example 2, except that in step (2), sludge ash is not added but sludge powder is directly pyrolyzed.

[0061] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 68 minutes of adsorption.

[0062] Comparative Example 4

[0063] The preparation method of the sludge-based composite adsorbent in this comparative example is the same as that in Example 2, except that in step (5), the mass ratio of the sludge-based molecular sieve, the sludge-based perovskite, and the sludge-ash-modified sludge-based pyrolytic carbon is adjusted to 1:1:8.

[0064] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 74 minutes of adsorption.

[0065] Comparative Example 5

[0066] The preparation method of the sludge-based composite adsorbent in this comparative example is the same as that in Example 2, except that in step (5) the three slurries are mixed and then sprayed.

[0067] The performance test conditions were the same as those in Example 2. The results showed that the adsorption was saturated after 61 minutes of adsorption.

[0068] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A sludge-based composite adsorbent, characterized in that: The sludge-based composite adsorbent comprises sludge-based molecular sieve, sludge-based perovskite and sludge-ash-modified sludge-based pyrolytic carbon.

2. The sludge-based composite adsorbent according to claim 1, characterized in that: The sludge-based molecular sieve, sludge-based perovskite and sludge ash-modified sludge-based pyrolysis carbon are compounded in a "sandwich" structure.

3. The sludge-based composite adsorbent according to claim 1 or 2, characterized in that: Based on the total amount of the sludge-based composite adsorbent, the sludge-based composite adsorbent comprises 20-30 weight percent of sludge-based molecular sieve and 20-30 weight percent of sludge-based perovskite, and the rest is sludge ash-modified sludge-based pyrolytic carbon.

4. The method for preparing the sludge-based composite adsorbent according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing sludge-based molecular sieve, sludge-based perovskite, and sludge ash-modified sludge-based pyrolytic carbon with a dispersant and a binder, respectively, to prepare slurry A, slurry B, and slurry C; (2) Slurry C, slurry B, and slurry A are sprayed on a substrate in sequence and dried to obtain the sludge-based composite adsorbent.

5. The preparation method according to claim 4, characterized in that: The dispersant is ethanol; the binder is Nafion solution; Preferably, the dosage ratio of the sludge-based molecular sieve to ethanol and Nafion solution is (2-3) g:10 mL:1 mL; the dosage ratio of the sludge-based perovskite to ethanol and Nafion solution is (2-3) g:10 mL:1 mL; the dosage ratio of the sludge ash-modified sludge-based pyrolytic carbon to ethanol and Nafion solution is (4-6) g:10 mL:1 mL; More preferably, the ratio of the sludge-based molecular sieve to ethanol and Nafion solution is 3 g:10 mL:1 mL; the ratio of the sludge-based perovskite to ethanol and Nafion solution is 2 g:10 mL:1 mL; the ratio of the sludge ash-modified sludge-based pyrolytic carbon to ethanol and Nafion solution is 5 g:10 mL:1 mL; Preferably, the substrate is one of nickel foam, carbon cloth and honeycomb ceramics.

6. The preparation method according to claim 4, characterized in that: The preparation method of the sludge-based molecular sieve is as follows: taking sludge ash, adding dilute hydrochloric acid to adjust the pH value to 1-2, stirring, filtering, and drying the filter residue to obtain tempered sludge ash; taking the tempered sludge ash, adding sodium hydroxide solid, grinding and placing in a tube furnace to calcine in an air atmosphere, adding distilled water to the obtained calcined solid for hydrothermal crystallization, filtering, and drying the filter residue to obtain the sludge-based molecular sieve; Preferably, the mass ratio of the quenched and tempered sludge ash to the sodium hydroxide solid is 1:(1-5); the calcination temperature is 600-900°C, and the calcination time is 1-3h; the mass ratio of the calcined solid to distilled water is 1:(5-20); the hydrothermal temperature is 80-120°C, and the hydrothermal time is 6-12h; More preferably, the mass ratio of the tempered sludge ash to the sodium hydroxide solid is 1:2; the calcination temperature is 700°C, and the calcination time is 1.5h; the mass ratio of the calcined solid to distilled water is 1:10; the hydrothermal temperature is 100°C, and the hydrothermal time is 10h.

7. The preparation method according to claim 4, characterized in that: The preparation method of the sludge-based perovskite is as follows: taking sludge ash, adding dilute nitric acid to adjust the pH to 1-2, stirring, filtering, adding polytitanium chloride to the filtrate, mixing, dehydrating, and pyrolyzing the obtained mixture under a nitrogen atmosphere to obtain the sludge-based perovskite; Preferably, the concentration of the dilute nitric acid is 0.5-2 mol / L; the mass ratio of the polytitanium chloride to the filtrate is (1-6):1; the pyrolysis temperature is 300-500°C, and the pyrolysis time is 2-6h; More preferably, the concentration of the dilute nitric acid is 1 mol / L; the mass ratio of the polytitanium chloride to the filtrate is 3:1; the pyrolysis temperature is 450° C., and the pyrolysis time is 3 h.

8. The preparation method according to claim 4, characterized in that: The method for preparing the sludge ash modified sludge-based pyrolytic carbon is as follows: taking sludge ash and sludge powder, mixing them, adding dilute hydrochloric acid to adjust the pH value to 1-2, stirring, filtering, and placing the obtained solid in a tubular furnace and calcining it under a nitrogen atmosphere to obtain sludge ash modified sludge-based pyrolytic carbon; Preferably, the mass ratio of the sludge ash to the sludge powder is 1:(5-10); the concentration of the dilute hydrochloric acid is 0.5-2 mol / L; the calcination temperature is 500-700°C, and the calcination time is 1-3h; More preferably, the mass ratio of the sludge ash to the sludge powder is 1:7; the concentration of the dilute hydrochloric acid is 1 mol / L; the calcination temperature is 600° C., and the calcination time is 2 h.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The method for preparing the sludge ash comprises: calcining and grinding municipal sludge in an air atmosphere to obtain sludge ash; Preferably, the calcination temperature is 700-900°C and the calcination time is 4-6h; More preferably, the calcination temperature is 800°C and the calcination time is 5 hours. The total mass fraction of silicon compounds and aluminum compounds in the sludge ash is ≥50%, and the mass fraction of iron compounds is ≥7%; The preparation method of the sludge powder comprises: drying and grinding the municipal sludge to obtain the sludge powder; Preferably, the drying temperature is 100-120°C; More preferably, the drying temperature is 105°C.

10. Use of the sludge-based composite adsorbent according to any one of claims 1 to 3 or the sludge-based composite adsorbent obtained by the preparation method according to any one of claims 4 to 9 in purifying sludge drying odor.

Citation Information

Patent Citations

  • Adsorbent prepared from residual sludge as well as preparation method and application thereof

    CN108607505A

  • Method for preparing sludge-based carbon zeolite functional material

    CN109621903A

  • Absorption / adsorption coupling enhanced stink and organic waste gas treatment method

    CN114210174A

  • Deodorizing adsorbent for municipal sludge drying treatment and preparation method thereof

    CN114225901A

  • Method for treating degradation-resistant organic wastewater by using printing and dyeing sludge carbon-based adsorbent

    CN115155522A